2022
DOI: 10.37349/etat.2022.00106
|View full text |Cite
|
Sign up to set email alerts
|

Steroid utility, immunotherapy, and brain tumor management: an update on conflicting therapies

Abstract: Steroid use is a widely accepted practice for both the treatment and prevention of tumor-induced edema, but there are many unknowns regarding their current clinical utility with modern anti-tumor therapies. This decreases edema and relieves the symptomatic mass effect. There are clearly understood benefits and commonly accepted complications of methylprednisolone (MP) use, but the topic is recently controversial. With immunotherapy advancing, a robust immune response is crucial for full therapeutic efficacy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 103 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Studies carried out by He and co-workers have reported high level of fatty acids in both the fruits and leaves (19). Most of the compounds identified are grouped into fatty acids, esters, alkaloids and terpenes, N-acetyl d,l-norleucenine enantiomer is use in the treatment of vertigo in part of Europe (44). Lochneridine belongs to the group of monoterpene indole alkaoids that have been identified in Catharanthus roseus and Tabernaemontana davaricata, they are known to have antimalarial, antiarrhythmic and anticancer properties (45), The presence of these compounds in the vines of PEFF with documented similar or different pharmacological activities, implies that the effect observed could be due to synergistic, additive or antagonistic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out by He and co-workers have reported high level of fatty acids in both the fruits and leaves (19). Most of the compounds identified are grouped into fatty acids, esters, alkaloids and terpenes, N-acetyl d,l-norleucenine enantiomer is use in the treatment of vertigo in part of Europe (44). Lochneridine belongs to the group of monoterpene indole alkaoids that have been identified in Catharanthus roseus and Tabernaemontana davaricata, they are known to have antimalarial, antiarrhythmic and anticancer properties (45), The presence of these compounds in the vines of PEFF with documented similar or different pharmacological activities, implies that the effect observed could be due to synergistic, additive or antagonistic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesise that pre‐treatment of hosts either with HDAC‐inhibitors or CGRPs will synergise with CAR‐T cells in targeting IL‐13Rα2 positive solid cancer for a better anti‐ tumour effect. In this regard, combination therapies consisting of concomitant use of the CAR‐T cell products with steroids or alternative agents such as bevacizumab, corticorelin and Boswellic acids are newly emerged areas of research where much effort is needed 60 . Studies that balance and optimise the aggressive anti‐tumour effects of CAR‐T cells with the opposing physiological effects of immunosuppression and oedema suppression, reparative effects of other alternative agents and additional anti‐tumour effects of agents such as bevacizumab or anti‐tumour oncolytic agents 61 may be beneficial for patients seeking cures as opposed to palliative measures.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that steroids play a role in reducing tumour-associated edema in the brain as well as reducing clinical signs associated with radiation induced necrosis. 31,32 The Radiation Therapy Oncology Group also found that in patients with brain metastases receiving radiation, those who received concurrent steroids had more rapid clinical improvement compared to those who did not. 31,33 We cannot form clinical conclusions of the role of concurrent steroid use and therapeutic outcome in our retrospective study of dogs with confirmed or presumed intracranial glioma.…”
Section: Discussionmentioning
confidence: 99%
“…; however, there are ongoing investigations into the clinical utility and efficacy. It is recognized that steroids play a role in reducing tumour‐associated edema in the brain as well as reducing clinical signs associated with radiation induced necrosis 31,32 . The Radiation Therapy Oncology Group also found that in patients with brain metastases receiving radiation, those who received concurrent steroids had more rapid clinical improvement compared to those who did not 31,33 .…”
Section: Discussionmentioning
confidence: 99%